An unusual cause of community-acquired pneumonia. (2018) - Mittal, Jaimie; Szymczak, Wendy A.; Robbins, Noah; Harris, Carol; Nori, Priya
Highlights: A. baumannii community-acquired pneumonia incidence and prevalence is unknown in temperate regions. It potentially has a rapidly progressive course and poor outcome. Progression of disease may be due to immune dysfunction in certain hosts. Studies are conflicting on the role and regimen of antibiotics on disease progression. Abstract: We present a case of fatal community-acquired pneumonia (CAP) due to Acinetobacter baumannii, which is rarely reported in the northeastern United States. Previously reported cases originate from tropical and subtropical climates, and infection tends to have an aggressive course with a poor outcome. Appropriate antimicrobial therapy is crucial; however, the associated systemic inflammatory response may overwhelm host defenses, especially in patients with certain co-morbidities.